Strategies and approaches in translating cultural Punjabi terms - Gurdial Singh, Kulwindr Kaur (Journal of Modern Languages, 2017)
This paper discusses approaches and strategies in translating various cultural kinship terms, sweets, jewellery etc. from English to Punjabi. This paper will show how these precise terms are able to convey the correct ambience and flavour for an accurate translation from English to Punjabi. This experience will help develop a useful methodology in translating cultural elements, and contributes towards the general theory of translation. It will suggest using the Skopos Theory by Vermeer, Oxford's (1990) Taxonomy of Language Learning Strategies, Sager's (1994) approaches to translating, Bell's (1991) translating strategies and Abdullah Hassan and Ainon Mohd.'s (2005) techniques for translating cultural items.